PENERAPAN MASHLAHAH MURSALAH DALAM ISU-ISU KONTEMPORER - Asriaty, Asriaty (Madania: Jurnal Kajian Keislaman, 2015)
Implementation of Maslahah Mursalah in Contemporary Issues. The present article is aimed at describinghow Islamic law anticipates occurring of contemporary problematics according to Maslahah Mursalah. Maslahahmursalah (public interest) can be made as an argument for Islamic law determining if it deal with manyrequirements such as maslahat is suitable with syara, maslahat is not contrary with the Qur’an, sunnah, and ijma,and maslahat is existing in daruriyat level or hajiyat that in same level with daruriyat. Maslahah mursalah is notindependent argumentation that stands alone from the Qur’an, Sunnah, and Ijma’, but it is one of the Islamicdeductive methodes. In brief, maslahah mursalah is not resource of Islamic law but it is a method of Islamic lawdiscovering. Assembling of maslahah mursalah as dalil for Islamic law determining, it makes many contemporaryproblems can be known and determined although their law status is not mentioned in the Qur’an and as-Sunnah.So, maslahah mursalah assembling makes Islamic law always appropriate whenever and wherever